Competitive Sports Anxiety, Healing Imagery and Achievement Goal; Mediating Role of Coaching Feedback in Young Pakistani Athletes - Yumna Ali; Syeda Farhana Kazmi (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Sports psychology is integral to be taught both in academic settings and on practical athletic fields. This study considers students who are part of the physical education and sports department, whose responsibilities are twofold. Practical implications of managing sports anxiety, recovering from the ordeal of rehabilitation injuries, and achieving sports goals are crucial aspects of coaching feedback.